2016
DOI: 10.2298/abs150512132v
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms from a peat bog on the Pester plateau (southwestern Serbia): New records for diatom flora of Serbia

Abstract: The distribution of diatoms was studied in three types of diatom communities (epiphytes, benthos and plankton) of a peat bog on the Pester plateau. The observed diatom flora inhabited all investigated communities, comprising in total 250 taxa in 53 genera. Among them, 45 taxa were new records for the Serbian diatom flora. Identified taxa belonged to different groups of algae, however alkaliphile diatoms were dominant. New ecological data for Encyonopsis minuta, Pinnularia isostauron and P. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Regarding to existence of the species in Turkish inland waters, Cymbella lanceolata, C. tumida, Cymbopleura amphicephala, Encyonema auerswaldii, E. minutum, E. prostratum, E. silesiacum and Encyonopsis microcephala were "common species" while, Encyonema ventricosum and Reimeria uniseriata were "rare species" in the waters (Solak et al 2012b, Gönülol 2016 (Bey & Ector 2013) and the species was also recorded newly for diatom flora of Serbia (Vidaković et al 2016). R. ovata occurs rarely in oligotrophic cold water (Levkov & Ector 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to existence of the species in Turkish inland waters, Cymbella lanceolata, C. tumida, Cymbopleura amphicephala, Encyonema auerswaldii, E. minutum, E. prostratum, E. silesiacum and Encyonopsis microcephala were "common species" while, Encyonema ventricosum and Reimeria uniseriata were "rare species" in the waters (Solak et al 2012b, Gönülol 2016 (Bey & Ector 2013) and the species was also recorded newly for diatom flora of Serbia (Vidaković et al 2016). R. ovata occurs rarely in oligotrophic cold water (Levkov & Ector 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Considering phytobentic algal diversity overview, we will stay with peat bogs, i.e. the Pešter peat bog, for which Vidaković et al [85] provided the most recent report on diatoms diversity, not only in benthos but also epiphyton and plankton. These authors reported extraordinary diatom taxa richness of the Pešter peat bog, in total 250 diatom species from 53 genera and 45 new taxa for Serbian diatom flora.…”
Section: Microalgae In Central and South Serbiamentioning
confidence: 99%
“…Diatoms are one of the most ubiquitous and diverse photosynthetic microorganisms in aquatic ecosystems [27] and one of the most widely represented algal groups in peat bogs (e.g., [28][29][30][31][32]). The diversity of diatoms in the peatlands of Europe is very high, with around 403 recorded taxa, and a majority representation of the genera Pinnularia (14%), Eunotia (10%), and Navicula (10%), with respect to the total number of taxa [28,29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], and with similar species numbers and compositions to those found in peatlands in other regions of the world due to the cosmopolitan nature of diatom species (e.g., [30,31,51,52]). However, knowledge about the ecology of diatom communities in peatlands is still insufficient compared with other types of wetlands [25].…”
Section: Diatoms In Peatland Ecosystemsmentioning
confidence: 99%